Analysis of The Use of Betawi Vocabulary and Indonesian Language Among Students of The University of Muhammadiyah Tangerang, Faculty of Islamic Religion Semester III - Azzahra, Maulida; Djuharie, Otong Setiawan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the use of Betawi and Indonesian vocabulary among third semester students of the Faculty of Islamic Sciences, University of Muhammadiyah Tangerang. This study used a descriptive quantitative approach, with data collected through an online questionnaire distributed via Google Form to 20 respondents. The research instrument used a 5-point Likert scale to measure the frequency of use of Betawi and Indonesian vocabulary as well as factors influencing language choice. The results of the study show that Betawi vocabulary is still predominantly used in informal communication among students, especially commonly used expressions such as gue/gua, lu, banget, and udah. In contrast, Indonesian is more often used in formal and academic contexts, especially when communicating with lecturers. Environmental factors, peer interaction, and social media exposure were identified as the main factors influencing the use of Betawi vocabulary. These findings reveal the existence of situational code mixing, where students can tailor their language choices according to the context of communication. Therefore, the use of Betawi and Indonesian vocabulary does not reflect linguistic conflicts but rather shows students’ linguistic awareness and social identity in urban environments.